A study of the key factors that influence the investment behaviour of persons who invest in Mutual Funds through SIP (International Journal of Food and Nutritional Sciences, 2022)
This study analyses the key factors that influence the investment behaviour of persons who invest in Mutual Funds through SIP. the study was carried out in Pune City, and 122 investors were selected using convenience sampling technique. The data was collected through structured questionnaire and analyzed using percentage, mean, standard deviation and multiple regression analysis. The results of the study indicate that all the four independent variables namely age, income, education and occupation have significant influence on investment behaviour of persons who invest in Mutual Funds through SIP. Further the findings of the study reveal that investors are also influenced by other factors such as perceived risks and returns, perceived ease of investing, and recommendation from others. This study can help asset managers better understand their target market and develop more investor-centric strategies.